Recycling of shredded printed circuit boards (PCBs) by two-phase moving wave conveyors - Mimouni, Chahinez (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The aim of this study is to demonstrate the viability of electrostatic separation of mixtures from shredded printed circuit boards (PCBs), in association with the X-ray fluorescence analysis, and simultaneously to examine how the efficiency of this method is influenced by the supply voltage, both in terms of amplitude and nature.Methods: The electrostatic separation technique is used by means of a two-phase moving wave conveyor with characterisation analysis using X-ray fluorescence in order to justify the efficiency of the process studied. Results: The results of this study can have practical implications for improving the recycling process of electronic waste, especially from printed circuit boards (PCBs). By optimizing the high voltage and understanding its effects on the electrostatic separation process, it may be possible to increase the efficiency and effectiveness of recycling valuable materials from electronic waste while reducing environmental impact.Conclusion: The XRF analysis of the samples reveals their distinct compositions. The variations observed are even more marked if the influence of the voltages applied on the electrostatic separation process is considered.
Keywords: recycling; environment; waste electrical and electronic equipment; two-phase moving wave conveyor; x-ray fluorescence; high voltage